Additional risk factors associated with thrombosis and pregnancy morbidity in a unique cohort of antiphospholipid antibody-positive patients. Issue 6 (20th March 2022) - Li, Chun; Zuo, Yu; Zhang, Song; Makris, Una E.; Karp, David R.; Li, Zhanguo
Abstract: Background: Antiphospholipid syndrome (APS) is an autoimmune prothrombotic condition with significant morbidity. The objective of this study was to identify additional clinical and epidemiological risks of arterial thrombosis, venous thrombosis, and pregnancy morbidities in a large cohort of persistent antiphospholipid antibodies (aPLs)-positive carriers. Methods: This was a cross-sectional cohort study of 453 consecutive patients with a documented positive aPL who attended Peking University People's Hospital. Among 453 patients screened, 297 patients had persistent positive aPL. We compared asymptomatic aPL carriers with thrombotic and obstetric APS patients. And the univariate analysis and multivariable logistic regression were used to evaluate the association between different risk factors and APS clinical manifestations. The levels of circulating markers of neutrophil extracellular traps (NETs) (cell-free DNA and citrullinated histone H3 [Cit-H3]) were assessed and compared among aPL-positive carriers with or without autoimmune disease and APS patients. Results: Additional risk factors associated with arterial thrombosis among aPL-positive carriers included: smoking (odds ratio [OR] = 6.137, 95% confidence interval [CI] = 2.408–15.637, P   =  0.0001), hypertension (OR = 2.368, 95% CI = 1.249–4.491, P   =  0.008), and the presence of underlying autoimmune disease (OR  =  4.401, 95% CI  =  2.387–8.113, P  < 0.001). Additional risks associated with venous thrombosis among aPL carriers included: smoking (OR  =  4.594, 95% CI  =  1.681–12.553, P   =  0.029) and the presence of underlying autoimmune disease (OR  =  6.330, 95% CI  =  3.355–11.940, P  < 0.001). The presence of underlying autoimmune disease (OR  =  3.301, 95% CI  =  1.407–7.744, P   =  0.006) is the additional risk, which demonstrated a significant association with APS pregnancy morbidity. Higher circulating levels of cell-free DNA and Cit-H3 were observed among APS patients and aPL patients with autoimmune diseases compared with those aPL carriers without underlying autoimmune diseases. Furthermore, control neutrophils that are conditioned with APS patients'sera have more pronounced NET release compared with those treated with aPL carriers'sera without underlying autoimmune diseases. Conclusions: We identified several potential additional risk factors for APS clinical manifestations among a large cohort of Chinese aPL carriers. Our data may help physicians to risk stratify aPL-positive Asian patients.